Staying At Home Or Moving To A Retirement Community After Covid-19 - et. al., Wong Ming Wong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study investigates the impact of the COVID-19 on the consumer's retirement choice regarding the Event System Theory and Theory of Planned Behavior. This study examines the consumer's retirement intention preference - staying or moving. The research question is that whether the COVID-19 event affects the consumer's retirement intention. This study aims to examine the relationship between the event strength of the COVID-19 pandemic consisting entirely of (a) the event novel, (b) the event critical, and (c) the event disruptive, and the consumer's intention. A Chinese professional research firm conducts an online survey to gather 981 respondents. The data obtained is analyzed by using the confirmatory factor analysis of the structural equation modeling. The findings reveal that the COVID-19 pandemic affects the consumer's retirement intention. The consumer tends to move to a retirement community instead of staying at home. The contribution of this study summarizes two. First, in practical operation, the enterprise is advised to minimize an unforeseen event on the consumer. Second, from the theoretical development, the consumer's experience of an unexpected event incorporates the purpose. The impact of an event on a consumer's experience leads to intention and behavior.